Methodology to increase the second year student's creativity of the Majoring at Physical Culture - Yudelqui Martínez-León; Ania Teresa Cordero-González; Ana Belkys Amador-Cabrera (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2013)
The research entitled ¨Methodology to increase the second year student's creativity of the Majoring at Physical Culture¨ has the goal to increase their creativity from the Pedagogy subject. This research offers a group of pedagogical and psychological bases about creativity that influence in the development of the student's personality. It also gives a set of actions aimed to increase the creative development through the Pedagogy lessons, as a main way of organizing the teaching learning process. In this investigation it is defined creativity as the process that expresses the professors´ skills in the teaching learning activity. The creative methodology was validated through the development of a pre-experiment. Besides there were used theoretical, empirics and statistics methods to prove the affectivity of this research. The final results of the investigation give the professors a pattern of performance so as to influence positively in their students´ behaviour according to the present demands of the Cuban society.